Analysis of Students' Learning Outcomes and Scientific Literacy Activities Using Guided Inquiry and Discovery Learning Models - Menti Irawati Purba; Ricky Andi Syahputra; Jamalum Purba; Ani Sutiani; Pasar Maulim Silitonga (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
This research aims to find out whether the Guided Inquiry learning model is better than Discovery Learning in improving scientific literacy activities and student learning outcomes on reaction rate material. The research method used is quasi experimental. The sample from this research consisted of two classes, namely experimental class I which was taught using the guided inquiry learning model, totaling 29 students and experimental class II, which was taught using the Discovery Learning model, totaling 27 students. The results of data analysis show that the average learning outcomes of students using Guided Inquiry (80.69) are higher than the average learning outcomes of students taught using the Discovery Learning model (74.63) and the average scientific literacy activities of students using Guided Inquiry (79.15 ) higher than the average using the Discovery Learning model (73.72). Hypothesis results using the right-hand t-test and α = 0.05 obtained tcount > ttable (2.34 > 1.675) for students' scientific literacy activities and tcount > ttable (2.49 > 1.675) for student learning outcomes so that in this study the null hypothesis (Ho) is rejected and the alternative hypothesis (H₂) is accepted. Thus, it was found that the Guided Inquiry learning model was better than Discovery Learning in improving scientific literacy activities and student learning outcomes on reaction rate material.